Bangladesh: Agricultural R&D Indicators Factsheet - Stads, Gert-Jan; Rahman, Md. Mustafizur; Nin-Pratt, Alejandro; Gao, Lang (International Food Policy Research Institute, 2019)
Agricultural research investment and human resource capacity in Bangladesh have grown considerably in recent years, largely as a result of increased government and World Bank funding. Despite this growth, Bangladesh still only invested 0.38 percent of its AgGDP in agricultural research in 2016—well below the level needed to address multiple challenges, including rapid population growth and severe climate change impacts. Although research staff numbers and qualification levels have gradually improved over time, an aging pool of PhD-qualified researchers remains as an important challenge.